2015
DOI: 10.1371/journal.pone.0127542
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Basal Ganglia Network Model Markers for Medication-Induced Impulsivity in Parkinson's Disease Patients

Abstract: Impulsivity, i.e. irresistibility in the execution of actions, may be prominent in Parkinson's disease (PD) patients who are treated with dopamine precursors or dopamine receptor agonists. In this study, we combine clinical investigations with computational modeling to explore whether impulsivity in PD patients on medication may arise as a result of abnormalities in risk, reward and punishment learning. In order to empirically assess learning outcomes involving risk, reward and punishment, four subject groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 135 publications
0
18
0
Order By: Relevance
“…PD patients with pathological gambling have likewise shown reward hypersensitivity compared to disease-matched controls, with antiglutamatergic therapy (amantadine) associated with decreases in reward hypersensitivity at least in a few patients (Cera et al ., 2014). Furthermore, network modeling studies of PD patients with ICDs on dopaminergic medication suggest that these patients are hypersensitive to reward compared to loss, while PD patients with ICDs not on dopaminergic medication were hypersensitive to loss but not to reward (Balasubramani et al ., 2015). Meanwhile, PD patients without ICDs showed no difference between reward and punishment learning (Balasubramani et al ., 2015).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%
See 1 more Smart Citation
“…PD patients with pathological gambling have likewise shown reward hypersensitivity compared to disease-matched controls, with antiglutamatergic therapy (amantadine) associated with decreases in reward hypersensitivity at least in a few patients (Cera et al ., 2014). Furthermore, network modeling studies of PD patients with ICDs on dopaminergic medication suggest that these patients are hypersensitive to reward compared to loss, while PD patients with ICDs not on dopaminergic medication were hypersensitive to loss but not to reward (Balasubramani et al ., 2015). Meanwhile, PD patients without ICDs showed no difference between reward and punishment learning (Balasubramani et al ., 2015).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%
“…Furthermore, network modeling studies of PD patients with ICDs on dopaminergic medication suggest that these patients are hypersensitive to reward compared to loss, while PD patients with ICDs not on dopaminergic medication were hypersensitive to loss but not to reward (Balasubramani et al ., 2015). Meanwhile, PD patients without ICDs showed no difference between reward and punishment learning (Balasubramani et al ., 2015). In another study, PD patients with ICDs were shown to exhibit hyposensitivity to loss (Piray et al ., 2014).…”
Section: Impulse Control Parkinson’s Disease and The Stn: Major mentioning
confidence: 99%
“…However, recent years see the emergence of two novel lines of investigation into PD pathogenesis. These approaches, that aim to understand the PD pathology at cellular and network level, mark a significant deviation from the traditional approaches (Rodriguez et al, 1998;Bolam and Pissadaki, 2012;Pissadaki and Bolam, 2013;Balasubramani et al, 2015aBalasubramani et al, , 2015bPacelli et al, 2015;Chakravarthy and Moustafa, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This lumped model of the previous subsection has been extended to the BG network model with the value and the risk functions computed by the medium spiny neurons (MSNs) in the striatum (Balasubramani et al, 2015a; Balasubramani et al, 2015b). Our earlier studies proposed that striatal DA1 receptor (D1R) expressing MSNs code for value function, while the MSNs coexpressing D1R-D2R code for the risk function (Balasubramani et al, 2015b).…”
Section: Modelmentioning
confidence: 99%
“…This lumped model of the previous subsection has been extended to the BG network model with the value and the risk functions computed by the medium spiny neurons (MSNs) in the striatum (Balasubramani et al, 2015a; Balasubramani et al, 2015b). Our earlier studies proposed that striatal DA1 receptor (D1R) expressing MSNs code for value function, while the MSNs coexpressing D1R-D2R code for the risk function (Balasubramani et al, 2015b). Whereas the D1R MSNs project via the direct pathway (DP) to GPi, the D2R and the D1R-D2R co-expressing MSNs project to the GPe in the indirect pathway (IP) (Albin et al, 1989; Hasbi et al, 2011; Perreault et al, 2011).…”
Section: Modelmentioning
confidence: 99%